2018
DOI: 10.1038/s41598-018-29353-2
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Iron level is Associated with Increased Mortality in Patients with Sepsis

Abstract: Iron is an essential nutrient for bacterial survival and thus higher iron levels may precipitate bacterial infections. We investigated the association between the serum iron level and prognosis in patients with sepsis by using the single-centre Medical Information Mart for Intensive Care III (MIMIC-III) database. Sepsis patients with iron parameters measured on ICU admission were included and stratified according to quartiles of serum iron levels. A total of 1,891 patients diagnosed with sepsis according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 28 publications
1
34
1
5
Order By: Relevance
“… 35 Low serum iron correlated with lymphopenia, and extremely low serum iron (~3 μmol/L) identified COVID-19 patients with severe respiratory hypoxemia, likely secondary to pulmonary damage. This hypoferremia is more profound than in previously reported cohorts of non-COVID-19 ICU patients, including those with sepsis, 36 , 37 indicating that extreme hypoferremia may be a particular feature of severe COVID-19 disease. IL-6 drives hepcidin expression, and an unbalanced inflammatory response of high IL-6 and relatively low type I and type III IFN associates with severe COVID-19 and poor outcomes.…”
Section: Discussioncontrasting
confidence: 50%
“… 35 Low serum iron correlated with lymphopenia, and extremely low serum iron (~3 μmol/L) identified COVID-19 patients with severe respiratory hypoxemia, likely secondary to pulmonary damage. This hypoferremia is more profound than in previously reported cohorts of non-COVID-19 ICU patients, including those with sepsis, 36 , 37 indicating that extreme hypoferremia may be a particular feature of severe COVID-19 disease. IL-6 drives hepcidin expression, and an unbalanced inflammatory response of high IL-6 and relatively low type I and type III IFN associates with severe COVID-19 and poor outcomes.…”
Section: Discussioncontrasting
confidence: 50%
“…Moreover, the functional associations of alterations in markers of iron metabolism and the prognosis of septic patients are still incompletely understood. Several reports have shown that parameters of iron metabolism are predictors for outcome in ICU patients [16][17][18][19]. Nonetheless, there is still the need for more reliable biomarkers to predict the survival in ICU patients and to combine these with established clinical scores.…”
Section: Introductionmentioning
confidence: 99%
“…Хелатирование железа было предложено в качестве потенциальной терапии полибактериального абдоминального сепсиса [56]. Известно, что лечение хелатированием железа способно ослаблять рост бактерий [57].…”
Section: железо и сепсисunclassified
“…В противовес сказанному другие исследования показали, наоборот, рост заболеваемости и смертности у пациентов, получающих переливание крови [56]. В исследование Р. Lan (2018) был включен 1891 больной с диагнозом «сепсис» по критериям сепсис-3, из которых у 324 был септический шок.…”
Section: решит ли трансфузия крови проблему анемии и метаболизма желеunclassified
See 1 more Smart Citation